Development and research of the topology of cooling baffles for blades of the axial carbon dioxide turbines - Komarov, I.I.; Vegera, A.N.; Bryzgunov, P.A.; Makhmutov, B.A.; Smirnov, A.O. (KU Publ., 2022)
Currently, there is an increase in average annual temperature and climate change across the various continents. Carbon dioxide emissions from energy facilities contributed to this condition. Implementation of oxyfuel cycles is a promising solution for reducing carbon dioxide emissions from the energy sector. To date, the most efficient oxy-fuel cycle is the Allam cycle. In this cycle supercritical carbon dioxide acts as a working fluid of the cycle, wherein СО2’s temperature upstream of the turbine is 1,150 °С and the pressure is 30 MPa. Due to the high temperature of the working fluid, it is necessary to cool first stages of the carbon dioxide turbine. The feature of considered cooling system in this turbine is that carbon dioxide being used as a refrigerant too. This paper investigated two topologies of convective cooling systems in the carbon dioxide turbine’s nozzle blade as well as considers an option for increasing the intensity of heat exchange through the use of helical ribbing in the cylindrical cooling baffle. Numerical simulation involving the ANSYS software package was performed for two topologies of the cooling baffles arrangement in the nozzle blade body: configuration 1 - with 17 baffles of 1 mm diameter, configuration 2 - with three baffles of the blade profile shape. Configuration 1 proved to be more efficient: the Nusselt number has a value of 117, and average value of the heat transfer coefficient on the refrigerant side is 6,413 W/m2∙K. The effect of using helical ribbing in the cooling cylindrical baffle of the blade under study was investigated, which enabled to reduce the metal temperature by 54 °С on average and doubled the heat transfer coefficient.
Keywords: cooling blade; supercritical carbon dioxide; oxy-fuel combustion power cycle; carbon dioxide turbine; rib turbulators; heat transfer